2016
DOI: 10.1038/srep28020
|View full text |Cite
|
Sign up to set email alerts
|

An Acinetobacter trimeric autotransporter adhesin reaped from cells exhibits its nonspecific stickiness via a highly stable 3D structure

Abstract: Trimeric autotransporter adhesins (TAAs), cell surface proteins of Gram-negative bacteria, mediate bacterial adhesion to host cells and extracellular matrix proteins. However, AtaA, a TAA in the nonpathogenic Acinetobacter sp. strain Tol 5, shows nonspecific, high adhesiveness to abiotic material surfaces as well as to biotic surfaces. AtaA is a homotrimer of polypeptides comprising 3,630 amino acids and forms long nanofibers; therefore, it is too large and structurally complex to be produced as a recombinant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 60 publications
(84 reference statements)
1
26
0
Order By: Relevance
“…The His‐tag was inserted into the predicted loop region originally located at the tip of the AtaA fiber before the N‐terminal Ylhead domain (Figure ). The fiber lengths could be estimated from purified AtaA fiber fragments (3CAtaAs; Yoshimoto et al, ), as shown in Figure (between the N‐terminus and FGG_5: 225 nm, between the N‐terminus and FGG_2: 180 nm, and between FGG_2 and FGG_5: 45 nm). Thus, HisA, ΔNHisB, and ΔNHisC were designed to generate the fibers with 225, 135, and 45 nm in lengths, respectively, on the host cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The His‐tag was inserted into the predicted loop region originally located at the tip of the AtaA fiber before the N‐terminal Ylhead domain (Figure ). The fiber lengths could be estimated from purified AtaA fiber fragments (3CAtaAs; Yoshimoto et al, ), as shown in Figure (between the N‐terminus and FGG_5: 225 nm, between the N‐terminus and FGG_2: 180 nm, and between FGG_2 and FGG_5: 45 nm). Thus, HisA, ΔNHisB, and ΔNHisC were designed to generate the fibers with 225, 135, and 45 nm in lengths, respectively, on the host cells.…”
Section: Resultsmentioning
confidence: 99%
“…The distances between the cell surface and the colloidal gold on the fibers (20 fibers), which were selected from ones localizing at the farthest places from the edge of cell surface on 2D TEM images, were measured as the actual fiber length. The general procedures of TEM followed the methods previously described (Yoshimoto et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tol 5, was previously isolated from a biofiltration process 14 . This bacterium shows high adhesiveness to various abiotic surfaces from hydrophobic plastics to hydrophilic glass and stainless steel, and also demonstrates autoagglutination through its peritrichate fiber protein AtaA 15 17 . AtaA is a member of the TAA family, which contains proteins that are usually involved in bacterial adhesion to host cells and extracellular matrix proteins such as collagen and fibronectin, as well as in autoagglutination, colonization, biofilm formation, and serum resistance 18 23 .…”
Section: Introductionmentioning
confidence: 99%